La « corruption » de la pythie chez Hérodote dans l'affaire de Démarate (VI, 60-84). Du discours politique faux au discours historique vrai: - Bonnechere, Pierre (Dialogues d'histoire ancienne, 2013)
In his “Story of Demaratus”, Herodotus presents the Pythia as having been corrupted by king Cleomenes of Sparta in order to expose his colleague Demaratus as a bastard and therefore unable to rule. The episode has often been regarded as realistic, if not altogether factual. However, a thorough study of the passage shows that the corruption of the Pythia is only one link in a great narrative chain of corruption in which the protagonists are all ultimately punished. Moreover, Herodotus’ account proves that, despite being corrupted, the Pythia nonetheless tells the truth even if no one initially recognizes it as such. In the final analysis, then, the mendacious political speech of Cleomenes proves to be true in the historical account of Herodotus as it remains impossible to separate the corruption of the Pythia from the larger narrative; impossible too to indict Delphi with dishonesty.